PERENCANAAN KOTA HIJAU YOGYAKARTA BERDASARKAN PENGGUNAAN LAHAN DAN KECUKUPAN RTH - Amalia Ratnasari; Santun R.P Sitorus; Boedi Tjahjono (TATALOKA, 2015)
Green City concept is a concept of sustainable urban development that harmonize the natural environment and man made environment as a response to environmental degradation. Actualizing the green city, one of its attributes green open space is strictly regulated in Law No. 26 Year 2007 about Spatial Planning. The total area of the city 30% must be used as green open space (RTH), 20% as public RTH and 10% as private RTH. The purposes of this research are identifying vast and distribution of land use and RTH existing in Yogyakarta city, analyzing the adequacy of RTH based on vast territory and total population, determining areas that could potentially be developed for RTH, and arranging development strategy toward to Yogyakarta Green City. Several methods were used in this research, among others : image interpretation and analysis the adequacy of RTH is calculated based on vast territory and total population. The results showed that RTH eksisiting is 584.45 ha or 17.78%, consisting public green open space covering an area of 329.63 ha and private green open space for 254.82 ha. Based on vast territory, Yogyakarta city still needs 390.55 ha of  green open space , while based on total population, green open space still lack for 220.91 ha. Potential area in Yogyakarta City is 30.94 ha. RTH development strategy of Yogyakarta City focused on maintaining and increasing the quality of existing RTH, adding unused area as public RTH and developing green corridor. This indicates that green open space in Yogyakarta city is not sufficient based on the standard needed toward Green City.